Alarm weariness among nurses and its connection to noise sensitivity in critical care units - Trisnaningtyas, Wenny; Indriyawati, Nina; Metasari, Sherly (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Intensive care unit (ICU) noise has been a longstanding issue, but noise levels exceeding the recommended range impact patients and staff. Nurses who experience alarm fatigue endanger patient safety because it can cause death due to ignoring emergency alarms. This study aims to determine between alarm fatigue and noise sensitivity nurses in critical care units. This study's design was a quantitative study with a cross-sectional with the method of total sampling. The alarm fatigues section was used to gather the data, The instrument developed by Torabizadeh et al. consists of 19 substances, with noise sensitivity assessed through an adaptation within Weinstein's noise sensitivity scale (WNS). Univariate analysis uses descriptive analysis, and bivariate analysis uses Spearman correlation. The exam revealed a strong correlation between noise sensitivity and nurses' alarm fatigue (p-value = 0.000; p-value <α; α = 0.05). Furthermore, the findings of this study also revealed correlation coefficient value of 0.780. Subjective evaluations suggest that increased noise levels in ICUs cause irritation, potentially leading to higher stress, decreased well-being, and lower performance. However, empirical data with objective and physiological measures are needed.